The relationship between family cohesion and adaptability and non-suicidal self-injury behavior in ethnic minority adolescents: a moderating mediation model - Lai, Junrong; Chen, Zhiyan (Frontiers in Psychology, 2023)
ABSTRACT：To explore the relationship between family cohesion and adaptability and non-suicidal selfinjury behavior among ethnic minority adolescents, as well as the mediating effect of depression and the moderating effect of school connectedness, this study adopted the Family Adaptability and Cohesion Scale, the Non-Suicidal Self-Injury Behavior Questionnaire, the Center for Epidemiological Studies Depression Scale, and the School Connectedness Scale to collect the behavioral data from 949 ethnic minority middle-school students. Descriptive statistical analysis and correlation analysis, as well as the mediating and moderating effects, were performed using SPSS 25.0 and Process macro program. We found that family cohesion and adaptability significantly and negatively predicted non-suicidal self-injury in ethnic minority adolescents (β=-0.28, p<0.001); depression mediated the relationship between family cohesion and adaptability and non-suicidal self-injury in minority adolescents, with a confidence interval (mediating effect size -0.15, and a Bootstrap 95% CI) of [-0.19, -0.12]. School connectedness moderated the second half of the mediating effect (β=-0.08, p<0.01).